Lean Hospital Management, Studi Empirik pada Layanan Gawat Darurat - Indrianawati Usman; Mira Ardiyana (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2017)
This research focuses on implementing lean management in hospital service, in order to elimination of waste to make a better performance.  It’s a qualitative single case study research. This study will identified waste and show how to reduce waste using lean management by empirically research in intensive care unit of Islamic hospital in Surabaya. Quantitative tools and measurement also used in this research using value stream analysis tools, and process activity mapping in order to identify the value added and non value added activities.  The results of the analysis indicate that there are seven kind of waste. Next the value stream analysis and process activity mapping show that the most frequent waste that cause ineffective performance of hospital service are waiting time, service defect and inappropriate process.